PENGARUH KUALITAS SUMBER DAYA MANUSIA, PENGAWASAN INTERN DAN SISTEM INFORMASI PENGELOLAAN KEUANGAN DAERAH TERHADAP KINERJA ORGANISASI PERANGKAT DAERAH (OPD) (Studi Empiris pada OPD Kabupaten Deli Serdang di Provinsi Sumatera Utara Periode 2016) - Novita, Novita; Kennedy, Kennedy; Hasan, Mudrika Alamsyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to test: 1) the influence of human resource quality on the performance of the organization of regional devices. 2) the influence of internal control on the performance of regional apparatus organizations. 3) influence of regional financial management information system on the performance of regional apparatus organization. The object of this research is 30 regional apparatus organization in Deli Serdang north Sumatera Province. Instruments in this study is a questionnaire distributed directly to respondents. Data analysis method used in this research is descriptive statistics, data quality test, classical assumption test, and hypothesis test consists of multiple linear regression analysis test, coefficient of determination and test F. The results showed that the quality of human resources, internal control and financial management information systems have a positif effect on the performance of regional organizations.Keywords : Quality of human resources, internal control and regional financial management information system